The Role Of Financial Reporting In Companies - Agustina, Ika (Yayasan Pendidikan Belajar Berdikari, 2024)
This study looks at how firms disclose their finances. Management may monitor a company's growth by participating in recording, accounting, and reporting. Thus, financial reporting based on a decision-making approach is an excellent instrument for measuring and monitoring a company's financial performance over time. Studying finance and other economic theories is vital for gaining a rapid comprehension of this concept. Accounting professionals must understand what